Factors Influencing Impulsive Buying of Paylater User in Generation Z in Indonesia - Tatiana, Anastasya Viviene; Wijaya, Christopher Eric; Adegea, Dio; Faizzah, Dyah Ayu Nur; Hakim, William; Suhartanto, Eko (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2025)
This study examined the impact of pay-later use among Generation Z in Indonesia and provided important insights into the psychological effects of this phenomenon. Technological developments in the financial sector have led to a breakthrough: pay later, a payment method that defers payment until the end of the month. In terms of the system employed, it is very similar to credit card use. Pay later is a breakthrough for people who do not have credit cards. This study aims to assess the factors influencing impulsive buying when using pay-later payment plans. We conducted a linear regression analysis on 50 responses collected from an online survey using non-probability sampling. The findings highlight the psychological impact of lifestyle pressures and weak self-control, which can lead to feelings of regret and financial stress that affect mental well-being.